2018
DOI: 10.1016/j.ebiom.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Re-Activation Suppresses Hepatic Steatosis but its Downregulation Does Not Promote Fatty Liver Development

Abstract: Nonalcoholic fatty liver disease is a highly prevalent component of disorders associated with disrupted energy homeostasis. Although dysregulation of the energy sensor AMP-activated protein kinase (AMPK) is viewed as a pathogenic factor in the development of fatty liver its role has not been directly demonstrated. Unexpectedly, we show here that liver-specific AMPK KO mice display normal hepatic lipid homeostasis and are not prone to fatty liver development, indicating that the decreases in AMPK activity assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
174
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(202 citation statements)
references
References 54 publications
19
174
2
7
Order By: Relevance
“…Although there is no clear evidence that polymorphisms in genes encoding AMPK subunits influence the occurrence of metabolic syndrome (26-28), a sustained decrease in AMPK activity has been found in the liver, skeletal muscle, and adipose tissue from obese or hyperglycemic rodents and humans in association with insulin resistance (29)(30)(31)(32)(33). Nevertheless, we have shown that liver-specific AMPK deficient mice display normal hepatic glucose and lipid homeostasis and are not prone to insulin resistance, suggesting that the decrease in AMPK activity associated with insulin resistance may be a consequence, rather than a cause, of changes in hepatic metabolism (10).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Although there is no clear evidence that polymorphisms in genes encoding AMPK subunits influence the occurrence of metabolic syndrome (26-28), a sustained decrease in AMPK activity has been found in the liver, skeletal muscle, and adipose tissue from obese or hyperglycemic rodents and humans in association with insulin resistance (29)(30)(31)(32)(33). Nevertheless, we have shown that liver-specific AMPK deficient mice display normal hepatic glucose and lipid homeostasis and are not prone to insulin resistance, suggesting that the decrease in AMPK activity associated with insulin resistance may be a consequence, rather than a cause, of changes in hepatic metabolism (10).…”
Section: Discussionmentioning
confidence: 64%
“…In the liver, AMPK plays a crucial role in the regulation of lipid partitioning between oxidative and biosynthetic pathways through the phosphorylation and inactivation of its well-established targets, acetyl-CoA carboxylase (ACC) 1/2 at Ser79/Ser212 residue and 3-hydroxy-3-methylglutaryl (HMG) coenzyme A (CoA) reductase (HMGCR) at Ser871 residue (8)(9)(10)(11)(12). The transition from the fasting to refed state is associated with modifications in hepatic lipid metabolism (i.e., increased fatty-acid synthesis and decreased fatty-acid oxidation) that appear to coincide with changes in the activation and phosphorylation of the AMPK !-subunit at Thr172 and ACC at Ser79 (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…58 More recent work has shown that metformin's ability to increase FAO (and inhibit lipogenesis) is enhanced when small-molecule AMPKspecific activators are used in combination with metformin in both rat and human primary hepatocytes. 59 These findings suggest that either (a) metformin does not robustly activate AMPK, or (b) metformin increases FAO independently of AMPK. Other studies have reported elevated gene expression of markers of FAO 60 and increased mitochondrial biogenesis in mice fed an HFD and treated with metformin, 28 which would potentially lead to greater oxidative capacity.…”
Section: Evidence That Metformin Increases Faomentioning
confidence: 96%
“…In primary rat hepatocytes, treatment with 0.5 mM metformin for 4 hours increased FAO (using 14 C‐oleate) and suppressed lipogenic gene expression via AMPK activation . More recent work has shown that metformin's ability to increase FAO (and inhibit lipogenesis) is enhanced when small‐molecule AMPK‐specific activators are used in combination with metformin in both rat and human primary hepatocytes . These findings suggest that either (a) metformin does not robustly activate AMPK, or (b) metformin increases FAO independently of AMPK.…”
Section: Mechanism By Which Metformin May Affect Ihtag Contentmentioning
confidence: 99%
“…It is important, however, to note that while the upregulation of AMPK protects against hepatic steatosis, its downregulation does not indicate susceptibility to hepatic steatosis (Boudaba et al. ).…”
Section: Introductionmentioning
confidence: 99%